Conformation and persistence length of chitosan in aqueous solutions of different ionic strengths via asymmetric flow field-flow fractionation. (1st November 2021) - Kang, Yu; Zhao, Xinyue; Han, Xintong; Ji, Xiangling; Chen, Quan; Pasch, Harald; Lederer, Albena; Liu, Yonggang
Abstract: Conformation of chitosan in acidic aqueous solutions is strongly influenced by ionic strength, but the conventional employed size exclusion chromatography is limited to high ionic strength. Here we show that conformation of chitosan in acetate buffer down to millimolar ionic strength can be studied via asymmetric flow field-flow fractionation (AF4), where the separation is governed by the diffusion properties of the chitosan molecules and assisted by the electrostatic repulsion of the polyelectrolyte from the channel membrane. The size of chitosan decreases with ionic strength due to increasing screening of the polyelectrolyte effect. The persistence length of chitosan in the solutions, obtained by fitting the conformation plot by the wormlike chain model, decreases linearly with the Debye screening length from 44.5 nm at a salt concentration of 1.25 mM dominated by the electrostatic contribution to 8.6 nm in 800 mM acetate buffer close to its intrinsic persistence length of 7.7 nm. Graphical abstract: Unlabelled Image Highlights: AF4 separation of chitosan is achieved in acetate buffer down to millimolar ionic strength. Chitosan adsorption is observed in SEC columns at ionic strengths below 100 mM. Persistence length of chitosan decreases from 45 to 9 nm with increasing ionic strength. Persistence length of chitosan has a linear dependence on the Debye screening length.